Perceived usefulness of ICT usage among JKKK members in Peninsular Malaysia - Abu Hassan, Musa; Abu Samah, Bahaman; Mohamed Shaffril, Hayrol Azril; Alby, Jeffrey Lawrence D'Silva (Canadian Center of Science and Education, 2011)
Information and communication technology (ICT) is indeed an important tool to expose the rural community to development. Realizing the importance of ICT, a number of high impact ICT programs and projects have been introduced by the government. However, do the rural community especially their leaders which are the Village Development and Security Committee members (JKKK) use ICT? And more importantly do they perceive ICT as useful in their daily activities and tasks? This question brings us to the main objective of this paper which is to know the factors that influence the perceived usefulness towards ICT usage among the JKKK members in Peninsular Malaysia. Besides, this paper intends to investigate the level of perceived usefulness towards ICT usage among JKKK members and to reveal the most significant contributors for perceived usefulness towards ICT usage. This is a quantitative study whereby data were gathered using a questionnaire. Based on the multi stage random sampling, a total of 240 JKKK members have been selected as the respondents. Based on the analyses done, it can be concluded that respondents studied do have a high level of perceived usefulness towards ICT usage. All of the four factors studied have a positive and significant relationship towards ICT usage. Attitude was identified as the most significant contributor for perceived usefulness towards ICT usage while the four predictor variables explain about 60.0% of the variance/variation in perceived usefulness towards ICT usage.